Sari Oneng Parakansalak Gamelan Tuning System and Its Comparison with Machjar’s Theory - Ega Fausta (ASSOCIATION FOR SCIENTIFIC COMPUTING ELECTRICAL AND ENGINEERING (ASCEE), 2019)
The research of measuring laras of Sari Oneng Parakansalak gamelan uses convergent parallel mixed methods. It attempts to find out the interval arrangement, which forms a scheme called laras system. This research give a provides clues about the existence of pelog gamelan in Sunda which is still debated until nowadays, which becomes the main reason why the writer is interested to measure the laras of Sari Oneng Parakansalak gamelan. In this research, laras theory of R.M.A. Koesoemadinata is used as the comparison to investigate what kind of laras is the laras scheme resulted from Sari Oneng Parakansalak gamelan’s interval arrangement. The result of this research is in form of persentation numbers which reveals the similarity between laras system of Sari Oneng Parakansalak gamelan and laras theory of R.M.A. Koesoemadinata. Besides giving a conclusion about the conformity between laras theory of R.M.A. Koesoemadinata and the fact found in the field, this research also informs about Sundanese pélog gamelan, which its existence is still hesitated/questioned by some Sundanese society. This study uses Da Tuner Lite which is validated with Korg Orchestral Tuner (OT-12) as the measuring instrument. The data of each waditra and the average of whole measured waditra are used to analyze the data of measurement result. From those two techniques, it can be detected that there are some waditra which are inappropriate to be used as samples. Therefore, the result of this study is taken from three waditra saron which indicates that Sari Oneng Parakansalak gamelan tends to have laras pélog djawar with its 87,19% of similarity. That result can also reveal that pélog gamelan really exists in Sundanese culture, proven by Sari Oneng Parakansalak gamelan which is made in Sumedang in 1825.